Volumetric, acoustic and transport properties of ternary solutions of l-serine and l-arginine in aqueous solutions of thiamine hydrochloride at different temperatures. (August 2019) - Rani, Ruby; Kumar, Ashwani; Sharma, Taniya; Sharma, Tanu; Bamezai, Rajinder K.
Graphical abstract: Highlights: Volumetric, acoustic and viscometric properties of amino acids in aqueous thiamine-HCl solutions were determined. Apparent molar volume and transfer volume were calculated and analyzed. Hepler's constant and d B /d T  suggests structure making behavior of both the amino acids in aqueous thiamine-HCl solution. The nature of solute-solute and solute-solvent interactions has been probed. Abstract: The volumetric, acoustic and viscometric properties are used for investigating the interactions ofl -serine andl -arginine in aqueous solutions of a vitamin, namely, thiamine hydrochloride, over a temperature range of (293.15–313.15) K and at atmospheric pressure. The limiting apparent molar volume, V 0 ϕ, and empirical parameter, Sv, is evaluated from apparent molar volume, Vϕ . Similarly, limiting apparent molar isentropic compression, K 0 ϕ, s, and slope, Sk, is evaluated from apparent molar isentropic compression, Kϕ, s . The corresponding transfer properties ( Δtr V 0 ϕ and Δtr K 0 ϕ, s ) from water to aqueous vitamin solutions are also evaluated. The viscosity data has also been used to analyze relative viscosity, ƞr, viscosity B -coefficients and temperature derivative of B -coefficients, dB / dT . The various calculated parameters assist to procure valuable information regarding the presence of different kinds of intermolecular interactions in the ternary (l -serine/l -arginine + water + thiamine-HCl) solutions.